2020
DOI: 10.3390/ijms21020551
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Gentamicin-Loaded Hydroxyapatite/Collagen Bone-Like Nanocomposite for Anti-Infection Bone Void Fillers

Abstract: A gentamicin-loaded hydroxyapatite/collagen bone-like nanocomposite (GNT-HAp/Col) was fabricated and evaluated for its absorption–desorption properties, antibacterial efficacy, and cytotoxicity. The hydroxyapatite/collagen bone-like nanocomposite (HAp/Col) powder was mixed with gentamicin sulfate (GNT) in phosphate-buffered saline (PBS) at room temperature. After 6 h mixing, the GNT adsorption in all conditions reached plateau by Langmuir’s isotherm, and maximum GNT adsorption amount was 34 ± 7 μg in 250 μg/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…Both COLL hydrogels were functionalized with GNT for the prevention and treatment of infection in osteomyelitis based on literature reports 42‐44 . Almost complete release of GNT from the GNT‐COLL/nHA hydrogel under physiological conditions (PBS pH 7.4, 37°C, Figure 3c) was achieved in 4 days, in line with literature data 45 . The in vitro study findings suggested potential of the hydrogels for the local treatment of mandibular OM, which has not been documented to date.…”
Section: Discussionsupporting
confidence: 71%
“…Both COLL hydrogels were functionalized with GNT for the prevention and treatment of infection in osteomyelitis based on literature reports 42‐44 . Almost complete release of GNT from the GNT‐COLL/nHA hydrogel under physiological conditions (PBS pH 7.4, 37°C, Figure 3c) was achieved in 4 days, in line with literature data 45 . The in vitro study findings suggested potential of the hydrogels for the local treatment of mandibular OM, which has not been documented to date.…”
Section: Discussionsupporting
confidence: 71%
“…The most frequently studied are hydroxyapatites substituted with ions and many of them have documented antimicrobial activity [ 8 , 9 ]. Another concept is combining hydroxyapatite and antibiotics, in which antimicrobial drug is released in the area of the application site where it inhibits microbial adhesion and growth [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noticing that a growing interest in multicomponent systems containing gentamycin and other antibiotics, hydroxyapatite, and collagen is currently observed. Such systems aim at the formation of the material providing the stable release of antibiotics while supporting bone-tissue growth [ 148 , 149 ]. For example, Ionescu et al [ 150 ] performed the synthesis of biocomposite materials consisting of hydroxyapatite, gentamycin, and collagen.…”
Section: Conjugates For Drug Deliverymentioning
confidence: 99%